(untitled) (Update Dental College Journal, 2016)
Accidental extrusion of sealer has been questioned regarding its fate, tissue reaction, and subsequent effect on the root canal seal and periradicular healing. These case reports demonstrate, radiographically, almost disappearance of excess sealer which has been expressed into the periradicular tissues during obturation and subsequent healing of periapical tissues despite this additional irritation. Update Dent. Coll. j: 2015; 5 (2): 52-56